Endovascular Treatment of Large or Giant Basilar Artery Aneurysms Using the Pipeline Embolization Device: Complications and Outcomes - Ge, Huijian; Chen, Xiheng; Liu, Kai; Zhao, Yang; Zhang, Longhui; Liu, Peng; Jiang, Yuhua; He, Hongwei; Lv, Ming; Li, Youxiang (Frontiers in Neurology, 2022)
Background This study aimed to investigate clinical and angiographic outcomes of Pipeline embolization device (PED) treatment of large or giant basilar artery (BA) aneurysms and examine associated factors. Methods Clinical and angiographic data of 29 patients (18 men, 11 women) with large or giant BA aneurysms were retrospectively examined. Mean age was 44.1 ± 21.2 years (range, 30–68). Mean aneurysm size was 22.2 ± 8.3 mm (range, 12.0–40.1). Results Mean angiographic follow-up was 18.3 ± 3.4 months (range, 4.5–60). The rate of adequate aneurysmal occlusion (O'Kelly–Marotta grade C–D) was 87%. The overall complication rate was 44.8%; most complications (84.6%) occurred in the periprocedural period. Univariable comparison of patients who did and did not develop complications showed significant differences in aneurysm size (p < 0.01), intra-aneurysmal thrombus (p = 0.03), and mean number of PEDs used (p = 0.02). Aneurysm size (odds ratio, 1.4; p = 0.04) was an independent risk factor for periprocedural complications in multivariable analysis. Mean clinical follow-up was 23.5 ± 3.2 months (range, 0.1–65). Nine patients (31%) had a poor clinical outcome (modified Rankin scale score ≥3) at last follow-up, including 7 patients who died. Univariable comparisons between patients with favorable and unfavorable clinical outcomes showed that aneurysm size (p = 0.009) and intra-aneurysmal thrombus (p = 0.04) significantly differed between the groups. Multivariable analysis showed that aneurysm size (odds ratio, 1.1; p = 0.04) was an independent risk factor for poor clinical outcome. Conclusion PED treatment of large or giant BA aneurysms is effective and can achieve a satisfactory long-term occlusion rate. However, the treatment complications are not negligible. Aneurysm size is the strongest predictor of perioperative complications and poor clinical outcome.